PENGARUH PEMANFAATAN KOPERASI TERHADAP TINGKAT KESEJAHTERAAN WARGA PADA KOPERASI SIMPAN PINJAM “KARYA AGUNG” BOJONEGORO - Rifky Ardhana Kisno Saputra; Endah Yuliani (LPPM UNISDA, 2019)
Cooperative business entities have the main goal not to seek profit but to serve members of the cooperative to be more prosperous based on the principle of family. The savings and loan cooperative